A SEM-X-Ray assisted experimental approach for the determination of mechanical and thermal load – induced damage in MMCs (Fracture and Structural Integrity, 2019)
An experimental technique is presented to evaluate mechanical and thermal load-induced microstructural damage, based on the Electron Probe Micro-Analysis (EPMA) principle, by which certain analytical potentialities of Scanning Electron Microscopy (SEM) are used. The aim of the study is to apply this technique in the case of metal matrix composites (MMCs). Based on earlier findings it is shown that by this technique the damage-controlled microstructural integrity distribution ahead of an edge-notch under tension is determined with sufficient reliability. To demonstrate this fact two MMCs were tested. Dog-bone specimens with an edge notch were subjected to slow tension up to their ultimate stress, the loading process was terminated and the EPMA technique was applied. The procedure was also applied after sudden cooling of the specimens by immersion in liquid hydrogen. It is shown that the MMC with larger differences between the elastic and plastic constants of the inclusion and the matrix exhibit increased proneness to mechanical and thermal load-induced damage. The findings obtained are discussed on the basis of the dominating combined influence of macro-microscopic mechanical and thermo-elastic stress concentration processes on the matrix-particle interfacial fracture strength.
Keywords: (Micro)-damage; X rays; MMCs; Thermal shock-stress; Process zone; Microstructural integrity